The Question of God and the Quest for God: Hans Jonas, Plato, and Beyond… - Spinelli, Emidio (Peitho. Examina Antiqua, 2020)
In reconstructing the conceptual universe of Jonas’s philosophy, a privileged place can, or indeed must, be reserved for his relationship with the classical heritage. More specifically, a crucial role is played by Plato, especially because, as Jonas strongly underlines, “with Plato (...) you have to go back a much greater distance to make him applicable to the present. But of course Plato is the greater one, the one we have to study again and again from scratch, the one we must discover (...). With Plato, you’re never finished, that’s the great foundation for all of Western philosophy”. In the light of this premise, this article will focus on the highly original use made in Jonas’s Der Gottesbegriff nach Auschwitz of the Platonic heritage, associated with the mythical figure of the Demiurge in the Timaeus.